Delivering non-hormonal contraceptives to men: advances and obstacles - Mruk, Dolores D. (2008)
There have been major advances in male contraceptive research during the past two decades. However, for a contraceptive to be used by men, its safety requires more stringent scrutiny than therapeutic compounds for treatment of illnesses because the contraceptives will be used by healthy individuals for an extended period of time, perhaps decades. A wide margin is therefore required between the effective dose range and doses that cause toxicity. It might be preferable that a male contraceptive, in particular a non-hormone-based compound, is delivered specifically and/or directly to the testis and has a rapid metabolic clearance rate, reducing the length of exposure in the liver and kidney. In this article, we highlight the latest developments regarding contraceptive delivery to men and with the aim of providing useful information for investigators in future studies.